2000
DOI: 10.1590/s0100-204x2000000800013
|View full text |Cite
|
Sign up to set email alerts
|

Progresso genético no melhoramento da aveia-branca no Sul do Brasil

Abstract: RESUMO -As cultivares de aveia-branca (Avena sativa L.) cultivadas no sul do Brasil até princípios da década de 80 eram provenientes do Uruguai e da Argentina, apresentando problemas de adaptação ao ambiente de cultivo. A partir dos anos 70, programas de melhoramento começaram a produzir suas próprias populações segregantes, possibilitando o lançamento em escala comercial de cerca de 35 cultivares. Com o objetivo de estimar o progresso genético nos programas de melhoramento de aveia-branca do sul do Brasil, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 4 publications
(9 reference statements)
0
8
0
10
Order By: Relevance
“…It is important to study genetic progress in hectoliter weight as it is a measure of grain quality (Lângaro and Carvalho, 2014) and considered a selection criterion in oat breeding programs in southern Brazil (Federizzi et al, 2005). During 1957to 1996, Barbosa Neto et al (2000 reported an annual genetic progress of 0.3% in the hectoliter weight of oat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to study genetic progress in hectoliter weight as it is a measure of grain quality (Lângaro and Carvalho, 2014) and considered a selection criterion in oat breeding programs in southern Brazil (Federizzi et al, 2005). During 1957to 1996, Barbosa Neto et al (2000 reported an annual genetic progress of 0.3% in the hectoliter weight of oat.…”
Section: Resultsmentioning
confidence: 99%
“…If required, this study can suggest possible changes in the strategies and methodologies used in plant breeding programs (Faria et al, 2007). For the oat crop, the studies developed by Barbosa Neto et al (2000) in Brazil and by Redaelli et al (2008) in Italy can be emphasized. In addition, the studies with cereals from the same family as wheat (Nedel, 1994;Rodrigues et al, 2007;Cargnin et al, 2008;Oury et al, 2012;Beche et al, 2014;Thomas and Graf, 2014;Wu et al, 2014), rice (Borges et al, 2009;Breseghello et al, 1999Breseghello et al, , 2011DoVale et al, 2012), and popcorn (Ribeiro et al, 2012) can be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…A aveia branca (Avena sativa L.) constitui uma fonte com potencial econômico de produção de grãos e qualidade nutricional para alimentação humana e animal, sendo considerada de grande importância como cultura de estação fria no Sul do Brasil (BARBOSA NETO et al, 2000). Desta forma, torna-se constante a necessidade para os melhoristas de aveia, disponibilizar permanentemente genótipos superiores com alta produtividade e que demonstrem estabilidade de produção.…”
Section: Introductionunclassified
“…Silva et al (2011) commented about the HI advantage in plant selection process or in the identification of more adjusted managements, indicating the efficiency with which the plant converts BY to straw and grain yield. Barbosa Neto et al (2000), while analyzing the HI of 15 white oat cultivars observed reduced variability in the character and detected a mean value of around 0.37. On the average, regardless of cultivar, sowing density and cultivation system, the HI value was around 0.46.…”
Section: Resultsmentioning
confidence: 97%